JENIS POLA ASUH ORANG TUA DAN TINGKAT KEBERHASILAN TOILET TRAINING PADA ANAK USIA 4-6 TAHUN - Sovia Nurlinda (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Toilet training is an attempt to train children to control urination (bowel movements) or bowel movements. At the age of 4-6 years the child is able to recognize the desire for BAK and BAB. One of the successes of toilet training is influenced by parenting parents. The purpose of the study was to determine the relationship between the types of parenting parents and the success rate of toilet training in children aged 4-6 years at TK Kemala Bhayangkari I Balikpapan. Descriptive analytic research method with cross sectional approach. Involved 80 respondents with the proportionate stratified sampling technique. Data analysis using chi square. The results showed that there was a relationship between the types of parenting parents and the level of success of toilet training in children aged 4-6 years in TK Kemala Bhayangkari I Balikpapan, based on data analysis the correlation value <α 0.05 was obtained. The type of parenting parents is one of the factors that influence the success of toilet training in children aged 4-6 years at TK Kemala Bhayangkari I Balikpapan. Therefore parents should not give strict treatment and be too relaxed in giving toilet training rules because children will tend to be stubborn, stingy, careless, emotional and arbitrary in carrying out activities.